2019
DOI: 10.1002/solr.201900133
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Vapor Post‐Annealing for Highly Efficient Sb2S3 Planar Heterojunction Solar Cells

Abstract: Solution‐processed Sb2S3 planar heterojunction solar cells have shown great progress in power conversion efficiency (PCE) in recent years. However, a conventional solution process yields Sb2S3 films with a small grain size. Herein, an alcohol vapor post‐annealing strategy is reported that uses alcohol vapors to facilitate grain growth of Sb2S3 films during annealing, achieving films with a larger grain size and better crystallinity. A series of alcohols with different polarities are used for the vapor post‐ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Noticeably, it has been well demonstrated that the Sb 2 S 3 crystallization for efficient solar cells normally takes place at 300−330 °C. [ 2,16–21 ] This article mainly focuses on the R effect on the Sb 2 S 3 film formation and the solar cell performance, and we fix the annealing temperature at 320 °C for the Sb 2 S 3 film crystallization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Noticeably, it has been well demonstrated that the Sb 2 S 3 crystallization for efficient solar cells normally takes place at 300−330 °C. [ 2,16–21 ] This article mainly focuses on the R effect on the Sb 2 S 3 film formation and the solar cell performance, and we fix the annealing temperature at 320 °C for the Sb 2 S 3 film crystallization.…”
Section: Resultsmentioning
confidence: 99%
“…The thickness of Sb 2 S 3 film (L) is linearly controlled by the concentration (C) and independent of the molar ratio R in the precursor solution (refer to Figure 4d). Noticeably, it has been well demonstrated that the Sb 2 S 3 crystallization for efficient solar cells normally takes place at 300À330 C. [2,[16][17][18][19][20][21] This article mainly focuses on the R effect on the Sb 2 S 3 film formation and the solar cell performance, and we fix the annealing temperature at 320 C for the Sb 2 S 3 film crystallization.…”
Section: Formation Of Sb 2 S 3 Filmmentioning
confidence: 99%
“…We test the conductivity of the pristine and modified SnO 2 films with an indium tin oxide (ITO)/ETL/Ag device (Figure 2a). The current conductivity (σ 0 ) could be calculated by the Equation (1) [42] 0…”
Section: Resultsmentioning
confidence: 99%
“…This could also partly explain why Sb 2 Se 3 usually exhibits much weaker photoluminescence (PL) signal compared with Sb 2 S 3 and kesterites. [ 19–22 ] Note that the limited QFLS attributed to the deep bulk defects and associated low carrier density could be one of the important reasons for the large open‐circuit voltage ( V OC ) deficit of Sb 2 Se 3 solar cells.…”
Section: Resultsmentioning
confidence: 99%